2013
DOI: 10.1111/dote.12023
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 is highly correlated with the differentiation and the prognosis of esophageal squamous cell cancer

Abstract: It's frequently stated that the pyruvate kinase M2 (PKM2) and Warburg effect are important for cancer development by accumulating more raw materials for macromolecule biosynthesis. However, the correlation between PKM2 and cancer is poorly reported. Here, we investigated the PKM2 expression in esophageal squamous cell cancer (ESCC). We observed that the expression of PKM2 was much higher in ESCC than in control normal tissue, and it is highly associated with many clinical features and prognosis. Specially, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Previously it has been reported that PKM2 behaves as a poor prognostic factor in signet ring cell gastric cancer and esophageal squamous cell cancer [19,20]. These tumors types were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it has been reported that PKM2 behaves as a poor prognostic factor in signet ring cell gastric cancer and esophageal squamous cell cancer [19,20]. These tumors types were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…PKM2, but not PKM1, is translocated into nucleus after EGFR activation and binds beta-catenin to regulate gene transcription [16]. Elevated expression of PKM2 has been reported in many types of cancers including colon and breast cancers [17,18] and is associated with poor prognosis in signet ring cell gastric cancer and esophageal squamous cell cancer [19,20]. As such, efforts were made to identify small molecule inhibitors specifically targeting PKM2 for anticancer therapy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these glycolytic enzymes may be regulated by tumorigenic factors or may regulate tumorigenesis in parallel. For one example, many glycolytic enzymes are highly correlated with tumor prognosis [5,1228]; for another example, hypoxia inducible factor-1 (HIF-1) is one of the key regulators of many glycolytic enzymes and of the Warburg effect [13,21,2935]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that heightened expression of PKM2 is critical for the maintenance of cancer cell growth and is associated with a poor prognosis in some types of cancer1920. On the other hand, it was previously thought that PKM1 is expressed in normal differentiated tissues and that the switching of PKM expression from PKM1 to PKM2 occurs during cancer development1821.…”
mentioning
confidence: 99%